ANALISIS KANDUNGAN ZAT BESI COOKIES SUBTITUSI TEPUNG JEWAWUT DAN TEPUNG IKAN TERI DALAM MENGATASI MASALAH ANEMIA GIZI BESI - suriani rauf; Mustamin Mustamin (Media Gizi Pangan, 2020)
ABSTRAK Basic Health Research Data (RISKESDAS) In 2013 the number of pregnant women with anemia was 37.1%, further discussed in the RISKESDAS data in 2018 the number of pregnant women with anemia increased to 48.1%. The program carried out by the government so far is the provision of Tablets Added Blood (TTD) for adolescent girls and pregnant women who cannot overcome the problem of anemia in pregnant women. Cake with the substitution of barley flour and anchovy flour is expected to increase the substance intake of pregnant women. This study aims to determine the efficacy and content of the substance of the substitution of barley flour and anchovy flour in overcoming the problem of iron nutrient anemia. This type of research is an experimental study with a post-test design research group design. This research is pre-experimental research with 3 variations of formulas and data analysis using the Friedman Test The best results of the cookie formula research are the concentration of 5%, laboratory test results of 5% reserve of cookie substances are 2.88mg / 100 gram, fulfilling 16% of the substance needs of women aged 18-49 years. Keywords: Cookies, iron content, barley flour, anchovy flour